Investigation of aircraft engine performance utilizing various alternative fuels - Warimani, Mahammadsalman; Azami, M. H.; Savill, Mark; Li, Yiguang; Khan, S. A.; Ismail, Ahmad Faris (IOP Publishing, 2019)
The airlines are subjected to the energy crisis and have raised environmental issues at the same time. Future engine technology advances could decrease the effect on the environment and energy consumption. Alternative fuelspotentially assist in the reduction of engine emissions and hence lower the energy-related issues. This study presents analysis of the efficiency of aircraft engines as a function of thrust force, flow of the and specific fuel consumption (SFC) at distinct mixing ratios (40% and 100%) of African natural gas, Algae, Camelina, Jatropa, Diesel, Hydrogen, Synthetic paraffinic kerosene, UK natural gas at cruising altitude. In – house Cranfield University simulation codes, PYTHIA & TURBOMATCH have been used to investigate and model a three-shaft high bypass engine analogous to RB211 - 524. The engine model has been certified and authenticated in commercial aircraft with open works found in the Bio - Synthetic Paraffinic Kerosene test program.Blended fuel of Kerosene & hydrogen (KE+HY) fuels gives values of 331.6 KN,1.2577KG/S, and 6.9512 kg/kwh for net thrust force,the flow of fuel and specific fuel feastingat mingling ratio of 40 % respectively. However, at mixing ratio of 100% Blended fuel of Kerosene & hydrogen (KE+HY) fuels gives values of 339.01 KN, 0.800KG/S, and 4.333 kg/kwh for net thrust, fuel flow, and specific fuel consumption respectively. It is found that blended fuel of Kerosene &hydrogen (KE+HY) fuels give better engine performances as compared to other alternative fuels. However, Kerosene &diesel (KE+DI) fuels have shown a slight reduction in engine performance.